Nuclear introgression without mitochondrial introgression in two turtle species exhibiting sex‐specific trophic differentiation. Issue 10 (12th April 2016) - Mitchell, Sarah M.; Muehlbauer, Laura K.; Freedberg, Steven
Abstract: Despite the presence of reproductive barriers between species, interspecific gene introgression has been documented in a range of natural systems. Comparing patterns of genetic introgression in biparental versus matrilineal markers can potentially reveal sex‐specific barriers to interspecific gene flow. Hybridization has been documented in the freshwater turtles Graptemys geographica and G. pseudogeographica, whose ranges are largely sympatric. Morphological differentiation between the species is restricted to females, with female G. geographica possessing large heads and jaws compared to the narrow heads of G. pseudogeographica females. If hybrid females are morphologically intermediate, they may be less successful at exploiting parental feeding niches, thereby limiting the introgression of maternally inherited, but not biparental, molecular markers. We paired sequence data with stable isotope analysis and examined sex‐specific genetic introgression and trophic differentiation in sympatric populations of G. geographica and G. pseudogeographica . We observed introgression from G. pseudogeographica into G. geographica at three nuclear loci, but not at the mitochondrial locus. Analysis of ∂ 15 N and ∂ 13 C was consistent with species differences in trophic positioning in females, but not males. These results suggest that ecological divergence in females may reduce the opportunity for gene flow in this system. Abstract : Our study couples stable isotope analysis with genetic sequence data to examine sex‐specific introgression and trophic differentiation in two hybridizing turtle species. We found that introgression occurs through males but is halted in females. Trophic differences in females may provide a mechanism that can contribute to reduced hybrid female fitness.